Perspectives on learning styles in motor and sport skills - MacMahon, C.; Fuelscher, I. T.; Ball, K. (Frontiers in Psychology, 2012)
We present the perspective that while coaches and instructors commonly adapt learning styles to maximize training outcomes, there has been little to no empirical support for the efficacy of this practice. Learning stylesis a learner`s preferred mode (e.g., visual, verbal) of taking in and processing new information. Although iti s a relevant topic for the learning of motor and sport skills, few studies have used an appropriate methodology to test the effectiveness of learning style-based instruction. We highlight the need for a learning style assessment tool specific to motors kills and call for a test of the learning style hypothesis, the claim that learners will benefit from instruction that is tailored to their individual learning style. To this end, we suggest methodological guidelines.